2022
DOI: 10.3390/nu14142994
|View full text |Cite
|
Sign up to set email alerts
|

Cutoff Points of Waist Circumference for Predicting Incident Non-Alcoholic Fatty Liver Disease in Middle-Aged and Older Korean Adults

Abstract: This study aimed to determine the optimal cutoff value of waist circumference (WC) for predicting incident NAFLD. In this community-based prospective cohort study, we analyzed data from 5400 participants without NAFLD at baseline aged 40–69 years. NAFLD was defined as a NAFLD-liver fat score >−0.640. A Cox proportional hazards regression model was used to estimate the hazard ratio (HR) and 95% confidence interval (CI) for an association between body composition and NAFLD incidence. The predictive power of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…A five-year study by S Wang et al including 12,477 observers showed that the cumulative incidence of MAFLD increased with increasing waist circumference and concluded that waist circumference was an independent risk factor for MAFLD [ 24 ]. A prospective cohort study in Korea involving 5400 people aged 40 ~ 69 years showed that waist circumference was the most important risk factor for MAFLD among the physical indicators of middle-aged and elderly people in Korea, and the threshold of waist circumference values were 81 cm for men and 78.5 cm for women [ 25 ]. Results of a clinical study on risk factors for NAFLD in Urumqi, China, showed that waist-to-hip ratio was a clinically meaningful risk factor for the development of NAFLD[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A five-year study by S Wang et al including 12,477 observers showed that the cumulative incidence of MAFLD increased with increasing waist circumference and concluded that waist circumference was an independent risk factor for MAFLD [ 24 ]. A prospective cohort study in Korea involving 5400 people aged 40 ~ 69 years showed that waist circumference was the most important risk factor for MAFLD among the physical indicators of middle-aged and elderly people in Korea, and the threshold of waist circumference values were 81 cm for men and 78.5 cm for women [ 25 ]. Results of a clinical study on risk factors for NAFLD in Urumqi, China, showed that waist-to-hip ratio was a clinically meaningful risk factor for the development of NAFLD[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Multi-Ethnic Study of Atherosclerosis reported that both WC (indicator for AO) and BMI (indicator for general obesity) are important risk factors of NAFLD, but WC better discriminates the risk for NAFLD [18]. In our previous study, we found that WC was the most significant risk factor of incident NAFLD among the various body composition variables (BMI, body fat, and skeletal muscle mass index) in middle-aged and older Korean adults [19]. A recent study conducted in Japan found that AO itself is significantly associated with NAFLD regardless of metabolic health status [20].…”
Section: Discussionmentioning
confidence: 87%
“…A meta-analysis found that individuals with abdominal obesity as measured by WC had a higher risk of NAFLD than did those with general obesity measured by BMI [ 27 ]. Another study also identified that WC was the most-significant risk factor for incident NAFLD among various body-composition variables in South Korean adults [ 28 ]. Visceral fat in abdominal obesity was independently associated with hepatic inflammation and fibrosis regardless of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%